Professionalism in the virtual environment: Exhausted scope review of evidences with concepts in medical education - Leili Mosalanejad; Saeed Abdollahifard; Mehdi Dastpak (Mashhad University of Medical Sciences, 2021)
Background: A review on medical articles and their multiplicity, as well as the studies on professionalism in the general and specially online mode in recent years shows the attention of medical training practitioners to this subject and their effort to overcome its possible threats. The aim of the present study was examining all the available evidences about e professionalism with an emphasis on medical education. Methods:  This study investigated the comprehensive review of evidences in their concepts. It was conducted in term of reviewing all texts related to e professionalism through all search engines between 2000 and 2018 in an online environment. Qualitative studies with the key words of e professionalism were searched from RISMA 2009 Flow Diagram. The evidences were extracted by mixing the results of different parts and their analyzing. Results: 237 articles were checked in the survey. After checking the quality and the adaption of titles with their concepts, 23 articles where chosen and proved for this study. Examining the evidences categorized the articles in the following fields: "Definition, concept and the importance of virtual professionalism, tools of testing professionalism in the virtual environment, people's perception and outlook of professionalism in virtual environment, inappropriate behaviors in using electronic environment and virtual networks, politics of explaining virtual professionalism, and the role of virtual environment in explaining medical professionalism". Conclusions: Due to the importance of professionalism in the virtual environment in definitions also a look at the importance of technology usage in education and therapy, paying attention to different dimensions of professionalism is necessary more than ever.